Imunoterapia contra pitiose: efeitos sobre os parâmetros imunológicos dos equinos. - Rocha, Jean Paul Santos (2013)
Pythiosis is a granulomatous, life-threatening disease of humans and animals, which is caused by the oomycete Pythium insidiosum. The treatment of the infections caused by this pathogen is complicated because of its cell wall and cytoplasmic membrane characteristics. Therefore, immunotherapy obtained from P. insidiosum culture extracts has emerged as an alternative treatment for equine pythiosis. Notwithstanding, the mechanisms by which immunotherapy work are not yet fully understood. The aims of this study were: a) to evaluate the immunological parameters in immunotherapy by measuring interleukin-2 (IL-2) and interferon-γ (IFN-γ) levels; b) to evaluate the biochemical parameters (hepatic function) in the horses of the experiment. To address this issue, 10 horses were divided in two groups: control (n=5), composed of animals without pythiosis; and infected (n=5), composed of animals with the disease. Animals from both groups received four doses of the immunotherapeutic product PitiumVac®. A significant increase in IL-2 and IFN- γ levels was observed after 42 days of immunotherapy in the infected group, and the animals were considered cured. The immunotherapy also improved the hepatic function of the animals, decreasing alanine aminotransferase and alkaline phosphatase levels. This may be a result of the interaction of different immunotherapeutic antigen present in the immune system, causing an increase in the production of these cytokines and establishing a predominance of TH1.